2021
DOI: 10.1177/1090198120985450
|View full text |Cite
|
Sign up to set email alerts
|

#TripleNegativeBreastCancer on Instagram

Abstract: Little is known about how triple negative breast cancer (TNBC) is discussed on the visual social media platform, Instagram. A greater understanding of the experiences of TNBC survivors that are documented on this platform may inform us of how this group of survivors cope with this rare, but aggressive form of breast cancer. This study analyzed a random sample ( N = 501) of Instagram posts using the hashtag #triplenegativebreastcancer. Using a quantitative content analysis, posts were coded for the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The result of this present study showed that 24% of posts emanated from individual accounts, detailing personal experiences. Similarly, previous studies examining the impact of social media on health information found that the posts were mostly generated by patients and involved the sharing of personal experiences [23,24]. Generally, patient experiences hold utility for prospective patients seeking insights into SCS.…”
Section: Discussionmentioning
confidence: 79%
“…The result of this present study showed that 24% of posts emanated from individual accounts, detailing personal experiences. Similarly, previous studies examining the impact of social media on health information found that the posts were mostly generated by patients and involved the sharing of personal experiences [23,24]. Generally, patient experiences hold utility for prospective patients seeking insights into SCS.…”
Section: Discussionmentioning
confidence: 79%
“…In conclusion, while so far the intentional use of Pinterest for health promotion purposes has been limited (public health organizations use the platform for some health promotion, studies indicate that so far this is not at a level sufficient to reach larger populations on the platform) (Guidry et al, 2019(Guidry et al, , 2020Henderson et al, 2018), the platform may hold greater potential for health promotion messaging as well as dissemination of healthy recipes for parents with young children, considering the use of Pinterest among parents.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies investigating the influence of social media on health conditions and interventions, the majority of posts were created by individual accounts and shared personal experiences [ 12 , 13 ]. This finding shows that patients use the Internet to disseminate medical information.…”
Section: Discussionmentioning
confidence: 99%